Aves de Rapina: de objeto a protagonista - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This article aims to analyze female representation in superhero films from the gender perspective used by Joan Scott, Laura Mulvey, and Chimamanda Ngozi. The work analyzes the 2020 film Birds of Prey: One Harley Quinn and her fantabulous emancipation, seeking to understand how it portrays female emancipation and the deconstruction of stereotypes. The analysis focuses on specific scenes from the film to explore aspects such as female rivalry, sisterhood, and the emancipation of the character Harley Quinn. The methodology used is based on a film analysis through historical and cultural conception. As a result, it is clear that a new perspective is emerging in superhero films, with an approach centered on women and valuing female protagonism. Thus, the study concludes that cinema acts as an active agent that influences the construction of new social representations and contributes to a society with equity
Keywords: Representação; Gênero; Cinema; Super-heróis; CNPQ::CIÊNCIAS HUMANAS